2022
DOI: 10.1039/d2nj03810b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced alkaline bifunctional electrocatalytic water splitting achieved through N and S dual-doped carbon shell reinforced Co9S8microplates

Abstract: Developing efficient, durable, and noble-metal-free electrocatalysts are considered the Holy Grail of sustainable hydrogen production through water splitting. In light of the potential importance of carbon components in low-cost electrocatalysis,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Along with D- and G-bands, a relatively weaker 2D-band also pops up in the Raman spectrum of 3D PNC in the region of 2300–3100 cm –1 , which further testifies to the improvement in local structural order . The 2D-band, also called the overtone of the D-band, results from a second-order two-phonon lattice vibration process and shows a strong frequency dependence on the excitation laser energy . The G- and 2D-bands are Raman signatures of graphitic sp 2 materials.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Along with D- and G-bands, a relatively weaker 2D-band also pops up in the Raman spectrum of 3D PNC in the region of 2300–3100 cm –1 , which further testifies to the improvement in local structural order . The 2D-band, also called the overtone of the D-band, results from a second-order two-phonon lattice vibration process and shows a strong frequency dependence on the excitation laser energy . The G- and 2D-bands are Raman signatures of graphitic sp 2 materials.…”
Section: Resultsmentioning
confidence: 80%
“…54 The 2D-band, also called the overtone of the D-band, results from a second-order two- phonon lattice vibration process and shows a strong frequency dependence on the excitation laser energy. 55 The G-and 2Dbands are Raman signatures of graphitic sp 2 materials. Table 1 summarizes the XRD and Raman analysis results of 3D PNC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Co 9 S 8 was also explored as a HER electrocatalyst many years ago because of its excellent metal conductivity [ 18 ]. By controlling the morphology and compounding with a conductive substrate, the HER properties of Co 9 S 8 -based materials have been greatly improved and have attracted a lot of attention [ 19 , 20 , 21 ]. Although much progress has been made, the low intrinsic activity of a single sulfide is still a factor limiting its application.…”
Section: Introductionmentioning
confidence: 99%
“…24–26 The catalyst shielding is another structural advantage offered by the high surface area hosts such as heteroatom-doped reduced graphene oxide. 27–29 Thus, extensive research has been reported on TMS-rGO hybrids as high-performance water-splitting catalysts benefitting from the above rationales. 30–33…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The catalyst shielding is another structural advantage offered by the high surface area hosts such as heteroatom-doped reduced graphene oxide. [27][28][29] Thus, extensive research has been reported on TMS-rGO hybrids as high-performance water-splitting catalysts benefitting from the above rationales. [30][31][32][33] In this work, we have successfully achieved the integration of the ideal structural features by conceptualizing a ternary hetero-catalyst consisting of a binary sulphide-sulphide (Co 9 S 8 / NiCo 2 S 4 ) system anchored on N-doped rGO through a multistep synthesis protocol (Scheme 1) involving a solvothermal method followed by the thermal treatment.…”
Section: Introductionmentioning
confidence: 99%